Opinion spam recognition method for online reviews using ontological features - Nguyen , Hoang Long; Pham , Hoang Trong Nghia; Ngo , Minh Vuong (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
Nowadays, there are a lot of people using social media opinions to make their decision on buying products or services. Opinion spam detection is a hard problem because fake reviews can be made by organizations as well as individuals for different purposes. They write fake reviews to mislead readers or automated detection system by promoting or demoting target products to promote them or to damage their reputations. In this paper, we propose a new approach using knowledge-based Ontology to detect opinion spam with high accuracy (higher than 75%).